Zinc finger protein Zn72D promotes productive splicing of the maleless transcript. - Worringer, K.A.; Panning, B. (Molecular and Cellular Biology, 2007)
In organisms with sex chromosomes, dosage compensation equalizes gene expression between the sexes. In Drosophila melanogaster males, the male-specific lethal (MSL) complex of proteins and two noncoding roX RNAs coat the X chromosome, resulting in a twofold transcriptional upregulation to equalize gene expression with that of females. How MSL complex enrichment on the X chromosome is regulated is not well understood. We performed an RNA interference screen to identify new factors required for dosage compensation. Using a Drosophila Schneider S2 cell line in which green fluorescent protein (GFP)-tagged MSL2 localizes to the X chromosome, we assayed approximately 7,200 knockdowns for their effects on GFP-MSL2 distribution. One factor identified is the zinc finger protein Zn72D. In its absence, the MSL complex no longer coats the X chromosome. We demonstrate that Zn72D is required for productive splicing of the transcript for the MSL protein Maleless, explaining the dosage compensation defect. However, Zn72D is required for the viability of both sexes, indicating its functions are not sex specific. Consistent with this, Zn72D colocalizes with elongating RNA polymerase II, implicating it as a more general factor involved in RNA metabolism.